Effects of prometryne on early life stages of common carp (Cyprinus carpio L.) - Velisek, Josef; Stara, Alzbeta; Koutnik, Dalibor; Machova, Jana (Pesticide biochemistry and physiology, 2015)
Toxicity of prometryne to early life stages of common carp was assessed. On the basis of accumulated mortality in the experimental groups lowest observed-effect concentration (LOEC) was estimated as 1100 µg/l; and no observed-effect concentration (NOEC) was 850 µg/l. Fulton's condition factor was significantly lower than in controls in fish exposed to 4000 µg/l after 7, 14, and 21 days. By day 14, fish exposed to 4000 µg/l prometryne showed significantly lower mass and total length compared to controls. Fish exposed the 1200 and 4000 µg/l showed delay in development, severe hyperaemia in gill, liver, and caudal and cranial kidney. Subchronic prometryne exposure of early-life stages of common carp at concentrations of 1200 and 4000 µg/l affected their survival, growth rate, early ontogeny, and histology.
Keywords: kapři; prometryn; Carps; Kidney; Embryo; zvířata; Liver; Triazine; Gills; Early development; Animals; žábry; chemické látky znečišťující vodu; Prometryne; Pesticides; Larvae; pesticidy; Histopathology; játra; Water Pollutants, Chemical; ledviny